Analysis Of Financial Performance Based On Profitability Ratio, Liquidity Ratio, Solvency Ratio, And Market Value Ratio At PT Gudang Garam Tbk In 2020–2024 - Ananda, Nelva; Amri, Rifki Hairul Amri; Hajar, Siti; Zalfa, Nadhira; Anwar, Khairul; Yusro, Laila; Nasution, Anggi Pratama (CV Raskha Media Group, 2025)
This study aims to analyze the financial performance of PT. Gudang Garam Tbk for the 2020-2024 period uses financial ratio analysis which includes profitability ratio, liquidity ratio, solvency ratio, and market value ratio. The research data is obtained from the company's annual financial statements published on the Indonesia Stock Exchange. The analysis method used is a quantitative descriptive analysis by calculating Current Ratio, Quick Ratio, Cash Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Return on Asset, Return on Equity, Net Profit Margin, Earning Per Share, Price Earning Ratio, and Price to Book Value in the financial performance report of PT. Gudang Garam Tbk which is listed on the Indonesia Stock Exchange (IDX) for the period of 2020 to 2024. The results of the ratio calculation from the financial statements will be interpreted to describe the company's profitability, liquidity, solvency, and market value. The results of the study show that the profitability ratio has decreased drastically with ROA decreasing from 10% (2020) to 1% (2024), ROE from 13% to 2%, and NPM from 6.6% to 0.9%, this states that the Company is in poor financial condition, with the risk of long-term financial difficulties if not addressed immediately. The Company's liquidity ratio fluctuates with the Current Ratio ranging from 183.2%-291.2%, which states that the Company has much larger current assets than current liabilities, specifically indicating very strong liquidity. The solvency ratio shows an improving capital structure in 2024 with a decrease in DAR to 27.1% and DER to 37.1%. The market value ratio shows a negative trend with EPS falling from 397.4% to 50.9%, PER increasing to 26.0%, and PBV decreasing to 0.4%, Where the company's financial health declined sharply, but its valuation in the stock market became expensive relative to its profits. This study concludes that PT. Gudang Garam Tbk faces serious challenges in maintaining profitability which may be caused by strict regulations in the tobacco industry, increasing cigarette excise, and changes in consumer behavior